Integrated management of web blight of urd and mung bean - DUBEY, S.C. (Indian Phytopathology, 2003)
The treatment combinations based on bio-agent Gliocladium virens (Trichoderma virens), Karanj (Pongamia glabra) cake, carboxin and Rhizobium were evaluated in integration of three methods as soil application,foliar spray and seed treatment for the management of web blight of urd (Vigna mungo) and mung (Vigna radiata) bean caused by Thanatephorus cucumeris (=Rhizoctonia solam) under sick field conditions. The integration of soil application of Karanj cake (2 q ha’), seed treatment with G. virens (10 6 spores/ml/10g seed) + carboxin (1 g kg-1)+ Rhizobium sp. (25 g kg-1seed) and foliar spray of Karanj leaf extract(10%) increased 35_7-36 % seed germination, reduced 92.4-93.7 % disease intensity and considerably enhancedplant vigour and grain yield of urd and mung bean. However, soil application of Karanj cake or G. virens multiplied on pulse bran-saw dust-tap water (3:1:4 w/w/v), seed treatment with G. virens +carboxin- Rhizobium, and foliar spray of Karanj leaf extract separately also proved effective for the managementof disease, but integration of any two was more effective than anyone alone.